Microwave dielectric analysis of human stratum corneum in vivo - Naito, Satoru; Hoshi, Masato; Yagihara, Shin (Biochimica et biophysica acta, 1998)
The dielectric properties of the human skin stratum corneum (SC) in the frequency range higher than 10 7 Hz are not well understood because of the difficulty in selective scanning of the SC area in vivo. The present study was carried out to make clear factors responsible for the dielectric properties using a measuring system specially developed for the study of SC [S. Naito, M. Hoshi, S. Mashimo, Anal. Biochem. 251 (1997) 163–172]. We found that the dielectric properties of SC can be expressed by the linear combination of two relaxation processes and d.c. conduction. The faster relaxation is that of free water. The slower relaxation and d.c. conduction were analyzed using a model assuming interfacial polarization between dissimilar materials. We concluded that the polarization is the origin of the slower relaxation process because the experimental data could be well interpreted according to the above mechanism. We also concluded that the polarization of swelled SC locates at the interface between SC cells and the intercellular lipid layer, or at the interface between the lipophilic and the hydrophilic part of the lamellar structured intercellular lipid layer.